New Information and Communication Technologies for Knowledge Management in Organizations 5th Global Innovation and Knowledge Academy Conference, GIKA 2015, Valencia, Spain, July 14-16, 2015, Proceedings - Palacios-Marqués, Daniel; Ribeiro Soriano, Domingo; Huarng, Kun Huang (Lecture Notes in Business Information Processing, 2015)
This book contains the refereed proceedings of the 5th Annual Global Innovation and Knowledge Academy, GIKA 2015, held in Valencia, Spain, in July 2015. The theme of the conference was "New Knowledge Impacts on Designing Implementable Innovative Realities." The GIKA conference offers a unique opportunity for researchers, professionals, and students to present and exchange ideas concerning management, information systems, and business economics and see its implications in the real world. The 13 contributions accepted for GIKA 2015 were selected from 102 submissions and include research that contributes to the creation of a solid evidence base concerning new information and communication technologies for knowledge management, measuring the impact and diffusion of new technologies within organizations, and highlighting the role of new technologies and tools in the relationships between knowledge management and organizational innovation.